The Quality Management of Norwegian Universities and its Influence on University Libraries - Salvesen, Helge (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2002)
In recent years many universities in the western world have been going through different crises, most notably of a financial nature. To date the reaction has been to set up evaluation schemes, to reorganise, to create strategic plans for teaching, research and promotion policy, whilst retaining the classic values of the university. What has not been clearly grasped is that the crisis is very largely one of relevance.